Point of care testing for group A streptococci in patients presenting with pharyngitis will improve appropriate antibiotic prescription. (3rd March 2016) - Orda, Ulrich; Mitra, Biswadev; Orda, Sabine; Fitzgerald, Mark; Gunnarsson, Ronny; Rofe, Geoff; Dargan, Anna
Abstract: Objective: History, clinical examination and throat culture may be inadequate to rule in or out the presence of group A streptococci (GAS) infection in patients with sore throat in a remote location. We correlated the diagnostic accuracy for guiding antibiotic prescription of clinical decision and physiological scoring systems to a rapid diagnostic point of care (POC) test result in paediatric patients presenting with sore throat. Methods: Prospective diagnostic accuracy study conducted between 30 June 2014 and 27 February 2015 in a remote Australian ED using a convenience sample. Among paediatric patients presenting with sore throat, the Centor criteria and clinical decision were documented. Simultaneously, patients without sore throat or respiratory tract infection were tested to determine the number of carriers. A throat swab on all patients was tested using a POC test (Alere TestPack +Plus Strep A with on board control), considered as reference standard to detect GAS infection. Results: A total of 101 patients with sore throat were tested with 26 (25.7%) positive for GAS. One hundred and forty‐seven patients without sore throat were tested with one positive POC test result (specificity 99%; 95% CI 96–100). Positive predictive value for clinician decision‐making for a positive GAS swab (bacterial infection) was 29% (95% CI 17–43), negative predictive value 78% (95% CI 63–88). Area under ROC for the Centor score was 0.70 (95% CI 0.58–0.81). Conclusion: Clinician judgement and Centor score are inadequate tools for clinical decision‐making for children presenting with sore throat. Adjunctive POC testing provides sufficient accuracy to guide antibiotic prescription on first presentation.